Langkah Kecil Untuk Sejuta Manfaat Bagi Lingkungan Masyarakat Desa Sempajaya Kabupaten Karo - Mula Sigiro; Juli Darmawati Zega; Regita Sari Situmorang; Tulus Frandika Sagala; Viona Pardila Br. Sembiring (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
The community service program (PKM) carried out by HKBP Nommensen Medan university students and their supervisors collaborates with the Sempajaya Village to help provide meaningful benefits and have a positive impact on the environment of the village community. Sempajaya Village is one of the villages in Berastagi subdistrict, Karo Regency, North Sumatra Province. In this village there are kindergartens, elementary schools, MTS and vocational schools. Access to this village is very easy to reach and public transportation often passes. This village consists of 9 hamlets. For the hamlet that we chose to implement PkM is hamlet 2. The work program was formulated together with the village government, with the aim of creating a clean and comfortable environment in Sempajaya village. things that they together want to achieve, especially in working together to clean up an environment, making cleanliness posters, opening a learning house for Sempajaya village school children and helping village officials can be carried out well.